Proton and lithium cation binding to some β-dicarbonyl compounds : a theoretical study - Burk, Peeter (Array, 2009)
Summary: DFT B3LYP/6-311+G** calculations were performed to study the proton and lithium cation binding to the acetylacetone, hexafluoroacetylacetone, diacetamide, and hexafluorodiacetamide. It was shown that the most stable Li+ adduct always corresponds to cyclic complex based on the trans, trans-keto form of the base. The product of protonation was found to be similar trans, trans-keto form based cyclic structure in case of diacetamide and hexafluorodiacetamide, while for acetylacetone and hexafluoroacetylacetone the protonation simply involves the addition of proton to (free) carbonyl oxygen in already cyclic enol form of the base with possible rotation of O−H bond